Fluid resuscitation in acute pancreatitis - Aydın Şeref Köksal; Erkan Parlak (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Köksal AŞ, Parlak E. Fluid resuscitation in acute pancreatitis. Turk J Gastroenterol 2017; 28: 322-3.